Pengaruh Media Sosial, Literasi Keuangan, dan Tren E-Commerce Selama Pandemi Covid 19 Terhadap Perilaku Konsumtif Mahasiswa (Studi Pada Mahasiswa Universitas Pembangunan Nasional “Veteran” Jawa Timur) - Nio Indra Satata; Muhadjir Anwar (Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of social media, financial literacy, and e-commerce models on consumptive behavior. During this pandemic period, students with high needs are also faced with conditions where lectures must be online and also online communication that makes high consumptive behavior. The method in this research uses stratification random sampling. Population in this study were all active undergraduate students at the National Development University